Restocking lobster air tawar (Cerax quadricarinatus) di Desa Wambarema, Poleang Utara, Bombana - Syair - syair; Muhammad Taufik Taufik; Rahim Aka Aka; Abdul Rahman Rahman; Yusnaini Yusnaini Yusnaini (Universitas Mataram, 2022)
Crayfish (Cerax quadricarinatus) is a new commodity for a partner in Wambarema Village. The carrying capacity of the land is suitable for cultivation. This commodity can become a new economic income for PPDM partners and the surrounding community. Since 2020 LAT has been introduced, and in 2021 LAT restocking will be carried out, aiming to accelerate the LAT population increase both in nursery and rearing ponds. The method used is technical guidance and scheduled assistance. The activity results show that the LAT population has started to increase, which is indicated by the growing LAT in the nursery pond. Although crayfish of number cannot be calculated precisely, LAT can adapt in breeding and rearing ponds. The average length of the lobster ranges from 11-15 cm, while the width of the head is about 3-5 cm. Partners responded well to the technical directions given by the implementation team and began to understand good ways of cultivating LAT. It is believed that LAT can become a new economic income for partners and the surrounding community